Regulatory Role of Heat Shock Proteins in the Pathogenesis of Type 1 and Type 2 Diabetes - Habich, Christiane; Sell, Henrike; Burkart, Volker (Current Immunology Reviews (Discontinued), 2017)
Diabetes is a severe metabolic disorder characterized by hyperglycemia due to defects in insulin secretion and/or insulin action. Over the past decades, a continuous rise of the incidence of diabetes is observed, leading to epidemic dimensions of the disease in large parts of the western world. Depending on the type of diabetes, (auto-)immune processes (type 1 diabetes) or metabolic disorders (type 2 diabetes) dominate the pathogenesis of the disease. Therefore, investigations aiming at the identification of disease mechanisms and the development of preventive and therapeutic approaches, focus on the identification of common regulators of both immunologic and metabolic pathways involved in the pathogenesis of diabetes. So far, extensive research, employing clinical and experimental approaches demonstrate a central role of heat shock proteins (HSPs) in diabetes development. In type 1 diabetes intracellular HSPs located in the beta cell can provide efficient protection against the deleterious effects of autoimmune effector mechanisms whereas extracellular HSPs can stimulate the release of beta cell damaging mediators from innate immune cells or even contribute to the induction of immune reactivity against beta cell specific antigens. In type 2 diabetes HSPs are involved in the control of various immunologic and metabolic processes contributing to the induction and maintenance of low-grade, subclinical inflammation associated with the development of diabetes and related disorders such obesity and insulin resistance. The results of current research on the pathogenesis of diabetes point to HSPs and HSP-dependent immunologic and metabolic pathways as promising targets for strategies to prevent or cure diabetes and its sequelae.
Keywords: type 2 diabetes